PUBLIC POLICIES IN BRAZILIAN EDUCATION: REALITIES, CHALLENGES, AND PERSPECTIVES (Interdisciplinary Studies Journal, 2025)
This paper addresses the complexity and challenges of public education policies in Brazil, focusing on policies aimed at basic education. The study discusses the role of the State in the formulation and implementation of these policies, analyzing key historical milestones, such as the creation of the Fund for the Maintenance and Development of Basic Education (Fundeb) and the National Education Plan (PNE), as well as specific programs such as the National School Feeding Program (Pnae). The qualitative documentary research highlights the importance of policies that promote educational equity and quality, but also identifies obstacles, such as lack of resources, administrative discontinuity, and regional disparities that compromise the effectiveness of the actions implemented. The analysis demonstrates that, despite advances, the sustainability and effectiveness of policies depend on a long-term commitment and integrated management between the federal, state, and municipal levels. Finally, recommendations are presented for the improvement of educational policies, emphasizing the need for strategic planning that considers regional specificities and ensures the inclusion of all students in the Brazilian educational system.
Keywords: Educational policies; Basic education; Inclusion; Regional inequality; Educational management